Identification of Dendrobium (Orchidaceae) in Liwa Botanical Garden Based on Leaf Morphological Characters - Mahfut Mahfut; Tundjung Tripeni Handayani; Sri Wahyuningsih; Sukimin Sukimin (Universitas Gadjah Mada, 2021)
Orchid is one of the most popular ornamental plants in the world. One of the orchid genera that is collected in a large number and known to have high morphological variations in the Liwa Botanical Garden is Dendrobium. However, to date, many Dendrobium collections have not been identified. Given the urgency of identification and the limitations of specimens in the field, especially flower organs, this study is important. This study aims to determine variations in morphological characters, phenetic relationships, and to identify Dendrobium collections based on leaf morphological characters in the Liwa Botanical Garden. Five accessions of Dendrobium were collected, namely CAT140, CAT 144, CAT 271, CAT 274, and IR015. Observation of 11 morphological characters leaves showed that leaf had high variations. The phenetic relationship based on the Gower similarity value and the UPGMA method shows that the Dendrobium in the Liwa Botanical Garden can be classified into 2 main groups formed with a similarity index value of 0.813. Based on Principle Component analysis values, it is known that the characters that have a large influence on grouping are the ratio of leaf length and width, leaf cross section, and leaf arrangement. The phenetic dendrogram topology is supported by the morphological character classification. The results of this study are expected to be basic information in the identification of natural orchids and conservation efforts in the Liwa Botanical Garden.